Assessment of endothelial dysfunction in Asian Indian patients with chronic kidney disease and changes following renal transplantation. (8th July 2014) - Sharma, Jugal; Kapoor, Aditya; Muthu, Ranjanee; Prasad, Narayan; Sinha, Archana; Khanna, Roopali; Kumar, Sudeep; Garg, Naveen; Tewari, Satyendra; Sharma, Raj K.; Goel, Pravin
Abstract Background Endothelial dysfunction may explain increased cardiovascular risk in patients with chronic kidney disease (CKD). Methods Brachial artery was imaged during reactive hyperemia (endothelium‐dependent, flow‐mediated dilatation, FMD) and during glyceryl trinitrate‐mediated dilatation (nitroglycerine‐mediated dilatation, NMD, endothelium‐independent) in 108 patients with CKD and three months following renal transplantation (RT) in 60 of them. Results Patients with CKD had significantly lower FMD vs. controls (9.1% vs. 18.3%, p < 0.001) while NMD was comparable (19.8% vs. 21.8%, p = ns). Impaired FMD (<4.5%) was observed in 26.8% patients with CKD and was more common in those on hemodialysis (HD; 28.4% vs. 15.4%) vs. those not on dialysis. FMD for patients with glomerular filtration rate (GFR) 15–60 vs. <15 mL/min/1.73 m2 was 12.9% and 8.8% (p = 0.05; respectively −29% and −52% lower vs. controls), indicating reduced FMD with increasing CKD severity. There was +72% increase in FMD following RT (9.1 to 15.7%, p < 0.001) while mean NMD was unchanged. Following RT, only 3.3% had impaired FMD. Conclusions Patients with CKD have endothelial dysfunction as evidenced by reduced FMD. Decreased FMD indicating worsening endothelial function was noted with increasing severity of CKD. Within three months of RT, there was significant improvement in FMD, while NMD values did not change.